AN ANALYSIS OF SWEARING WORDS USED IN 9Gag.com - Santi, Meita Ervi; Setyawan, Agustinus Hary (Annual International Conferences on Language, Literature, and Media, 2023)
Swearing plays a significant role in daily conversations among humans, both in oral and textual communication, and occurs frequently on the internet, typically featured by informal language and spontaneous writing. Therefore, this study aims to discover the types and functions of swear words that appear on the internet, especially on 9gag.com, the website that provides memes or humor to entertain users. This research used a descriptive qualitative method to achieve the research objectives. The source of data is the users' comments on 9gag.com related to COVID-19 over three months. The theory of Anderson and Trudgill (1990) for the types of swear words and the theory of Ljung (2011) about the function of swear words were used to analyze the data. This research found all types of swear words: expletive, abusive, humorous, and auxiliary. There were only 8 out of 14 functions that appeared in this research. The intention of using swear words by the users of 9gag.com is to express someone's emotion or feeling, for instance, anger, frustration, joy, and surprise.